"The Human Tide Mounts High”: Indymedia and Genoa’s G8 in 2001 (Cinéma & Cie. Film and Media Studies Journal, 2024)
Throughout this paper, I will focus on the media-documentation of Genoa’s G8 protests in 2001. More precisely, I will delve into the role of Indymedia Italia in the development of Genoa Social Forum’s Media Center, also referring to two of the most relevant videos produced by them and now collected in the online repository NGV – New Global Vision. In other words, I aim to highlight the aesthetic and political stances of a specific media collective during one of the most relevant historical events at the beginnings of the 21st Century.
Keywords: Genoa’s G8; Social Movements; Media Activism; Indymedia; Digital Video